The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/10502550902970546
|View full text |Cite
|
Sign up to set email alerts
|

Finding “Me” Again: Women's Postdivorce Identity Shifts

Abstract: The purpose of this study was to explore women's identity shifts as they navigate their postdivorce lives. We conducted in-depth, loosely structured interviews with 31 women who had been through at least 1 divorce. Interviews included questions about how women experienced life after divorce, specifically addressing changes they made to separate from the marriage and form a postdivorce identity. Patterns emerged regarding the process of identity change in 3 distinct domains: physical appearance, physical surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
(16 reference statements)
1
27
0
1
Order By: Relevance
“…As Gregson and Ceynar (2009) learned from women who divorced, there can be a desire to move on by making changes in physical surroundings and appearance that might also result in divorced individuals changing their view of themselves and consequently their social network.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As Gregson and Ceynar (2009) learned from women who divorced, there can be a desire to move on by making changes in physical surroundings and appearance that might also result in divorced individuals changing their view of themselves and consequently their social network.…”
Section: Discussionmentioning
confidence: 97%
“…Gregson and Ceynar (2009) interviewed 31 divorced women and found that their physical appearance often changed after divorce as the women struggled with their identity. Changing friendships and social networks could also be a part of that identity change.…”
Section: What Happens With Divorcementioning
confidence: 98%
“…The model of living for the children provides further accounts for the initial five years of transition processes and how these women move through stages and transitions are explained. Second, the major similarity among the models and the findings in this study is the importance of reconstructing or redefining a new identity in post-divorce adjustment (Baum, Rahave, & Sharon, 2005;Gregson et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…First, the study results not only support for those models but also provide further understanding of how these women make transitions to their new life of working single mothers. Although there is a large body of research on marital dissolution and post-dissolution adjustment, the mechanisms by which people make adjustment have been much less studied (Fasching, 2011;Gregson & Ceynar, 2009). The models in comparison (Guttmann, 1993;Radford et al, 1997) acknowledge the complexity and multidimensionality of the post-divorce transitions but except four-phase staging, dimensions after legal separation were simplified and their sub-stages were not explained.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, they become recognised by others and recognise themselves as full members of the community, contributing to it by asking and answering questions, taking part in forum discussions, and offering and receiving support. At the same time, they develop a view of themselves as a divorcing person, an understanding of possible emotional, practical and legal trajectories through the divorce experience, and an increased sense of cohesion and control in relation to the identity shifts that accompany divorce (Frieman, 2002;Sakraida, 2005;Willen & Montgomery, 2006;Kramrei et al, 2007;Gregson & Ceynar, 2009).…”
Section: Learningmentioning
confidence: 99%